ADAM28 is elevated in humans with the metabolic syndrome and is a novel sheddase of human tumour necrosis factor-a - Jowett, J.; Okada, Y.; Leedman, P.; Curran, J.; Johnson, M.; Moses, Eric; Goring, H.; Mochizuki, S.; Blangero, J.; Stone, L.; Allen, H.; Mitchell, C.; et al. (2012)
Metalloproteinases are implicated in cleaving numerous proinflammatory mediators from the cell surface. Interestingly, the elevated levels of tumour necrosis factor-α (TNF-α) have been associated with the metabolic syndrome. We aimed to ascertain whether the human metalloproteinase ADAM28 correlates with parameters of the metabolic syndrome and whether ADAM28 is a novel sheddase of human TNF-α. To identify novel metalloproteinases associated with the metabolic syndrome, we conducted microarray studies on peripheral blood mononuclear cells from a well characterised human cohort. Human ADAM28 and TNF-α were overexpressed and ADAM28 expression or activity was reduced with small-interfering RNA (siRNA) or pharmacological inhibition. TNF-α levels were measured in cell supernatant by enzyme-linked immunosorbent assay. We also conducted ADAM28 inhibition studies in human THP-1 macrophages. Human ADAM28 expression levels were positively correlated with parameters of the metabolic syndrome. When human ADAM28 and TNF-α were overexpressed in HEK293 cells, both proteins co-localised, co-immunoprecipitated and promoted TNF-α shedding. The shedding was significantly reduced when ADAM28 activity was inhibited or ADAM28 expression was downregulated. In human THP-1 macrophages, endogenous ADAM28 and TNF-α were co-expressed and TNF-α shedding was significantly reduced when ADAM28 was inhibited by pharmacological inhibition or siRNA knockdown. Our data suggest a novel mechanistic role for the metalloproteinase ADAM28 in inflammation, obesity and type 2 diabetes.